Graphene doping to enhance the mechanical energy conversion performances of GR/KNN/P(VDF-TrFE) flexible piezoelectric sensors. Issue 2 (19th December 2022) - Zhang, Xiaofang; Xia, Weimin; Cao, Congjun; Che, Peipei; Pan, Hong; Chen, Yuanqing
Abstract : By graphene doping, the output voltage of a flexible piezoelectric sensor based on the GR/KNN/P(VDF-TrFE) composite film is improved to 15.4 V when a 2.5 MPa impulse stress is applied on the surface of the sample. Abstract : Flexible piezoelectric composite, combining high piezoelectricity of filler and flexibility of polymer, provides a new research idea for developing flexible piezoelectric sensors (FPSs) with high piezoelectric output performance. FPSs based on GR/KNN/P(VDF-TrFE) three-phase composites are fabricated via doping a mass fraction of 15 wt% potassium sodium niobate (KNN) ceramic powder and various contents of graphene (GR) nanosheets into a P(VDF-TrFE) matrix. We find that an appropriate amount of GR is responsible for the enhanced crystallinity and β-phase of P(VDF-TrFE). When the GR content is 0.15 wt%, the three-phase composite film exhibits a dielectric constant ( ε r ) of 20.9 and a quasi-static piezoelectric constant ( d 33 ) of −28.4 pC N −1 . Under three different test scenarios of a ball drop experiment, a surface of the mouse wheel, and an action of 2.5 MPa external stress, this GR/KNN/P(VDF-TrFE)-based FPS shows high piezoelectric output voltages of 7.4 V, ∼2.0 V, and 15.4 V, respectively. Moreover, the FPS retains its performance even after an extended period of cantilever vibration cycles (2200). Thus, the conductive filler GR is responsible for promoting the energy conversion performance of the piezoelectric polymer, which also provides an application candidate of this GR/KNN/P(VDF-TrFE) film in FPSs.